Profit Efficiency in EU FADN Farms under Different Types of Agriculture - Łukasz Kryszak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the paper was to assess the profit efficiency in representative farms in FADN regions operating in various types of agriculture. For this purpose, clusters of FADN regions with relatively similar dominant types of agriculture were selected on the basis of their partial productivity indicators. Then, efficiency indicators were calculated for each region, using various types of DEA models. The data were adapted from FADN and covered the 2004 and 2015 period. On the basis of analysis conducted in the article, it was found that the farms located in Mediterranean regions were the most efficient. At the same time, in the cluster covering the regions with the most modern agriculture, the efficiency was at a very low level. Farms in most regions operated under the conditions of decreasing economies of scale, although the efficiency of scale itself improved. Moreover, in contrast to 2004, an increase in efficiency in relation to the best practice frontier was observed in 2015.